THE DETERMINANTS OF ENTREPRENEURIAL INTENTION OF EMPLOYEES IN TURKEY - YURTKORU, EMİNE SERRA; BÖRÜ, MELİHA DENİZ (FUTURE ACAD, 2019)
Entrepreneurship has gained an increasing popularity in Turkey. Entrepreneurial intention is increasing among young generations. Entrepreneurs, especially female entrepreneurs are supported by government and NGO's. Also there is a change in society values on the continuum between traditional and modern. The increase in modern values is expected to increase entrepreneurship as well. The aim of this study was to explore the determinants entrepreneurial intention of employees in Turkey. Based on literature it is suggested that generation, gender and society values will have impact on the entrepreneurial intention. Data collected form a sample of 1363 working employees from Istanbul were analyzed and results indicated male and GenY employees have more entrepreneurial intentions as expected. When society values were analyzed, originally unidimensional scale, emerged into two factors as modern and traditional. All participants had both modern and traditional values however modern values were higher. Interestingly employees with high traditional values had more entrepreneurial intention than employees with modern values. Interactive effect of these variables and also some other demographical variables were also tested and showed significant results. We hope our results will provide useful implications for policy makers. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Gender; generation; entrepreneurial intention; modern-traditional values; GENDER; GENERATIONS; STUDENTS; RISK